Students’ Perceptions of Wayground-Based Gamification in English Grammar Class - Muhammad Rifqi Syamsuddin; Harnita Rosalia (Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
The use of gamification in language learning has become increasingly popular as an innovative strategy to improve students’ engagement and motivation in the classroom. This study aims to investigate students’ perceptions of gamification through Wayground in English Grammar classes. The study employed a mixed-method approach involving quantitative and qualitative data collection. The participants consisted of 40 students enrolled in English Grammar classes. Data were collected through a Likert-scale questionnaire and open-ended responses distributed via Google Forms. The findings revealed that most students had positive perceptions toward the implementation of gamification in grammar learning. The majority of participants agreed that Wayground made grammar lessons more interesting, enjoyable, and interactive. Students also reported that gamified activities increased their motivation, participation, and classroom engagement. In addition, competitive features and instant feedback encouraged students to become more active during learning activities. Qualitative responses showed that many students considered grammar learning through games to be less stressful and more enjoyable compared to traditional teaching methods. However, several challenges were also identified. Some students stated that internet connectivity and technical issues affected their learning experience. A few participants also mentioned that competition sometimes created pressure or reduced their focus on understanding the material. Moreover, several students still preferred a combination of gamified and traditional grammar teaching to achieve better comprehension of grammar concepts. Overall, the study suggests that gamification through Wayground can create a more engaging and enjoyable learning environment in English grammar classes while still requiring balanced instructional strategies and adequate technological support.